Analysing peak flow attenuation in an urban wetland - Giermek, Monica Grace (Department of Environmental and Geographical Science, 2016)
Worldwide urbanization and climate change are influential in changing precipitation patterns and hydrological flow resulting in event driven urban flooding. The approach to flood protection has recently shifted from engineered and technical solutions to more sustainable and integrated solutions, by considering social, ecological and physical implications and exploring sustainable urban drainage options. Attenuation of peak stormwater flow using natural wetlands is one of many sustainable urban drainage methods used to reduce flooding and is an approach of interest for this research. The study site is located within the small, urbanized river system of the Liesbeek River in Cape Town, South Africa, which is prone to localized flooding during annual winter rainfall events. The study measures the attenuation capacity of a small-scale wetland adjacent to an urban river using a 2D PCSWMM hydrodynamic model. Research is focused on illustrating the attenuation capacity of this wetland. The model ran historic flow data to determine the attenuation capacity and to measure peak flow reduction. While the reduction is not sufficient to reduce damaging floods, the findings provide new knowledge and understanding of the attenuation capacity of this wetland and motivation for expanding sustainable urban drainage within the catchment. The study aims to build a baseline dataset for the research site with the data available at present. Peak flow of the Liesbeek River was reduced in scenarios with the Valkenberg Wetland present to accept on a portion of this flow. Attenuation was most effective for rainfall events with sudden spikes in peak flow, where a 42 per cent reduction of peak flow was observed. For a scenario with lower flow rates yet a prolonged peak flow rate, the wetland was less effective, with a 20 per cent reduction observed. This wetland was found to have the potential to provide valuable ecosystem services to the area by attenuating peak flow and thus reducing the occurrence of property damaging flooding downstream.